Genetic Ties and Affinity: Longitudinal Interviews on Two Mothers' Experiences of Egg Donation in Japan. Issue 2 (1st June 2019) - Shirai, Chiaki
Abstract: As of July 2017 twenty-four women who became mothers after receiving donated eggs have participated in an interview study entitled "The Experiences and Attitudes of Mothers Who Have Received Donated Eggs." Two of these women have been participating in the survey for more than five years. Focusing then on these two women, analysis revealed that their attitudes toward egg donation and genetic relationships changed over the course of their pregnancy, childbirth, and child rearing. Each woman chose eggs from donors who were similar to herself, as closeness and resemblance would bring affinity and certainty of the child's roots; the donor's egg is a substitute for her own and produces a pseudo-kinship between mother and child. Carrying and delivering the child made each woman feel biological ties with her child. However, by the time they entered the child-rearing stage, the women had to face the absence of any genetic ties. They felt compelled to tell the truth to their children, and to raise the children to be sufficiently strong enough to endure being told, yet at the same time the women began to attach less importance to genes. Thus, the ideas of genetic ties held by women who became mothers through egg donation changed.